Sanitary assessment and sensory evaluation of rice puto sold in the University of the Philippines Visayas, Miagao campus. - Opong, Gracia Gil L.
Rice puto from the two producer-vendors (PVA and PVB) in UPV, Miagao Campus were evaluated in terms of physico-chemical properties (pH and moisture content), microbiological qualities (TPC,YMC, fecal coliform, Staphylococcus aureus), and sensory characteristics (acceptability and attributes) an hour and 6 hours after production. The sanitation practices of PVA and PVB were also assessed. These producer-vendors differed in their processing methods, storing of ingredients and practice of hygiene and sanitation. Good sanitation practices were not strictly implemented by the producer-vendors. Proper sanitation of equipment and personnel hygiene were lacking from handlimg of raw materials to processing and packaging of the product. This reflected lack of proper training and awareness. Results indicate the high bacterial count had nosignificant difference among the rice puto from PVA and PVB an hour after and 6 hours after production (Two- Way ANOVA at 95% confidence interval). Yeast and mold count had a significant difference among the rice puto from both producer-vendor (PVA and PVB) an hour and 6 hours after production (Two- Way ANOVA at 95% confidence interval). Positive detection for E. coli and S. aureus were observed in the product which can linked to poor hygiene and handling of the producers. ANOVA at 95% confidence interval revealed that there was no significant difference in the MPN of fecal coliform in the rice puto from both producer-vendors (PVA and PVB) an hour and 6 hours after production. Sensory acceptability of rice puto for both PVA and PVB had no significant change and was perceived as like moderately an hour and 6 hours after production. It is recommended that the University of the Philippines Visayas Community should thoroughly inspect and monitor the producer-vendors selling inside the campus in a regular basis to ensure the safety of the consumers.